2013
DOI: 10.1038/ng.2821
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation of CDKN1B in small intestine neuroendocrine tumors

Abstract: The diagnosed incidence of small intestine neuroendocrine tumors (SI-NETs) is increasing, and the underlying genomic mechanisms have not been defined for these tumors. Using exome/genome sequence analysis of SI-NETs, we identified recurrent somatic mutations and deletions in CDKN1B, the cyclin-dependent kinase inhibitor gene, which encodes p27. We observed frameshift mutations of CDKN1B in 14 of 180 SI-NETs, and we detected hemizygous deletions encompassing CDKN1B in 7 out of 50 SI-NETs, nominating p27 as a tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
274
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(310 citation statements)
references
References 49 publications
31
274
4
1
Order By: Relevance
“…Carrying on WES, therapeutically relevant candidate alterations were found. (Francis et al 2013) found in a larger cohort of 180 SI-NET including 48 cases from Banck and coworkers heterozygous frame shift mutations of CDKN1B in 14 of 180 tumours (8%). CDKN1B encodes the p27 protein, which regulates cell cycle progression (Figs 2 and 3) (Polyak et al 1994).…”
Section: Small Intestinal Netmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrying on WES, therapeutically relevant candidate alterations were found. (Francis et al 2013) found in a larger cohort of 180 SI-NET including 48 cases from Banck and coworkers heterozygous frame shift mutations of CDKN1B in 14 of 180 tumours (8%). CDKN1B encodes the p27 protein, which regulates cell cycle progression (Figs 2 and 3) (Polyak et al 1994).…”
Section: Small Intestinal Netmentioning
confidence: 99%
“…Mutations of PTEN were found in 7.3% of PanNET and more recently mutations in TSC2, 8.8%; PIK3CA, 1.4% were also described (Perren et al 2000. TP53 mutations are rare in PanNET Jiao et al 2011, Cao et al 2013, Francis et al 2013, Cancer Genome Atlas Research 2014, Fernandez-Cuesta et al 2014, Cromer et al 2015, Lichtenauer et al 2015, Witkiewicz et al 2015, Scarpa et al 2017.…”
Section: Cellmentioning
confidence: 99%
“…DNA mutation analysis: whole-exome and targeted CDKN1B sequencing Exome sequencing was performed by Joshua Francis on 1 mg DNA as previously described (3). In brief, exonic region capture was performed utilizing the Agilent V2 capture probe set, and sequencing of 76-bp paired end reads was performed utilizing Illumina HiSeq2000 instruments.…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
“…The most frequent genomic event identified in SINETs is loss of heterozygosity (LOH) at chromosome 18, occurring in 60% to 78% of tumors (2,3); more recently, recurrent mutations in the cell cycle regulator CDKN1B (cyclin-dependent kinase inhibitor 1B) have been identified in approximately 8% of tumors in large-scale sequencing studies (3,4). Mutations occurring in CDKN1B are loss-of-function truncating mutations that occur throughout the gene.…”
Section: Introductionmentioning
confidence: 99%
“…CGH was essential in identifying the X chromosome defects in X-LAG, whereas WES was unsuccessful in identifying the causative gene [16]. And there is a fourth reason, entirely clinical, that the CDKN1B gene promoter findings are significant: germline CDKN1B defects are responsible for MEN4 and other endocrine tumors [6,7] and somatic mutations are found frequently in sporadic small intestine neuroendocrine tumors (SI NETs) [17] among other neoplasms. Do the findings by Sambugaro and Di Ruvo et al mean that patients with CDKN1B promoter defects are at risk for additional neoplasms?…”
mentioning
confidence: 99%